1988
DOI: 10.1159/000195493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Immunological Parameters in Interstitial Lung Disease by Discriminant Analysis

Abstract: In 37 subjects affected by interstitial lung diseases (19 patients with pulmonary sarcoidosis, 11 with hypersensitivity pneumonitis, 7 with idiopathic pulmonary fibrosis), we have compared by discriminant analysis (Statistical Package for the Social Sciences, version 8.3) 17 biological parameters derived from bronchoalveolar lavage analysis, gallium-67 scanning and lung biopsy. The aim of the study was to analyze the parameters of these three groups by forming one or more linear combinations of the discriminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Gallium scans have long been utilized for diagnosis and monitoring of HP and other interstitial lung diseases [Bernstein et al, 1983;Niederman and Matthay, 1983;Bisson et al, 1987;Galietti et al, 1987;Rom et al, 1987;Vanderstappen et al, 1988;Nimkin and Oates, 1989;Kahn et al, 1994;Baughman and Fernandez, 1996], although their efficacy has been questioned by some investigators [Bertorelli et al, 1988;Leonard and Templeton, 1992]. At first glance, our results would appear to agree with the latter groups, and suggest that gallium is of little value for diagnosis of HP.…”
Section: Discussionsupporting
confidence: 68%
“…Gallium scans have long been utilized for diagnosis and monitoring of HP and other interstitial lung diseases [Bernstein et al, 1983;Niederman and Matthay, 1983;Bisson et al, 1987;Galietti et al, 1987;Rom et al, 1987;Vanderstappen et al, 1988;Nimkin and Oates, 1989;Kahn et al, 1994;Baughman and Fernandez, 1996], although their efficacy has been questioned by some investigators [Bertorelli et al, 1988;Leonard and Templeton, 1992]. At first glance, our results would appear to agree with the latter groups, and suggest that gallium is of little value for diagnosis of HP.…”
Section: Discussionsupporting
confidence: 68%
“…It has been shown that gallium is delivered to the site of acute inflammation bound to transferrin (Tsan 1985;Klech et al 1987) and remains there by becoming associated with neutrophils, bacteria or various proteins (Tsan 1985). In the pneumoconioses, there is evidence to support the association of gallium uptake by the lungs with macrophages (Bisson et al 1983(Bisson et al , 1987Begin et al 1986;Rom et al 1987), neutrophils (Bisson et al 1987) and, to a lesser extent, lymphocytes (Bisson et al 1987), while in idiopathic pulmonary fibrosis, abnormal gallium uptake has been reported to be associated with neutrophils Klech et al 1987;Bertorelli et al 1988;Gibson et al 1989) and macrophages Vergnon et al 1987). Studies looking at the mechanisms responsible for gallium uptake, however, have tended to include few patients with diffuse lung disease associated with connective tissue diseases, a condition which may have a different aetiology and perhaps therefore a different pathophysiology compared with other forms of interstitial lung disease.…”
Section: Introductionmentioning
confidence: 98%
“…In previous studies, immunological parameters have been included in discriminant analysis [6,21] of the different ll...D. Thus, BERTORELLr et al [6] regard T-lymphocyte subpopulations, PMN and eosinophils in BALF, immune complex determination and gallium-67 lung scanning to possess the most important discriminant capacity. However, our study is not quite comparable with the above-mentioned study, because it included other variables and non-BALF parameters, and the use of different inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study is not quite comparable with the above-mentioned study, because it included other variables and non-BALF parameters, and the use of different inclusion criteria. The EAA population of BERTORELLI et al [6) was recently exposed to the causative antigen, and the authors do not state whether patients who had a BAL after provocation were also included. This is very important, because of the reported influence of the timing of BAL related to the last antigen exposure on the results of BALF analyses [11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation